2022
DOI: 10.1155/2022/7250278
|View full text |Cite
|
Sign up to set email alerts
|

miR-3059-3p Regulates Glioblastoma Multiforme Radiosensitivity Enhancement through the Homologous Recombination Pathway of DNA Repair

Abstract: Background. Glioblastoma multiforme (GBM) is one of the most deadly and recalcitrant illnesses of the neurocentral nervous system in humans. MicroRNAs (miRNAs) are a class of noncoding RNAs that play important roles in the regulation of gene expression and biological processes, including radiosensitivity. In this study, we demonstrated the relationship between miR-3059-3p and radiation in GBM. Materials and Methods. Radioresistant (RR) cells were obtained by exposing GBM8401 cells to 80 Gy radiation in 20 week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 38 publications
0
0
0
Order By: Relevance
“…It has been identified that miR-3059-3p regulates radioresistance by targeting DNA2 and controlling homologous recombination pathways through Rad51 & 52. MiR-3059-3p-mediated downregulation of DNA2 inhibited the HR pathway, making GBM cells more radiosensitive [82]. Glioma cell proliferation is inhibited and senescence-related genes p53, Cdkn1a, and Cdkn2c are upregulated after delivery of miR-34a.…”
Section: Several Mechanisms Of Drug Resistance Include Dysfunctional ...mentioning
confidence: 99%
“…It has been identified that miR-3059-3p regulates radioresistance by targeting DNA2 and controlling homologous recombination pathways through Rad51 & 52. MiR-3059-3p-mediated downregulation of DNA2 inhibited the HR pathway, making GBM cells more radiosensitive [82]. Glioma cell proliferation is inhibited and senescence-related genes p53, Cdkn1a, and Cdkn2c are upregulated after delivery of miR-34a.…”
Section: Several Mechanisms Of Drug Resistance Include Dysfunctional ...mentioning
confidence: 99%